The Effectiveness of Semi-Scripted Role Play in Enhancing Speaking Skills of Students at MAN 1 Palu - Lufita Sari; Muhammad Arid; Moh. Abraham Eisenring; Mochtar Marhum (Journal of General Education and Humanities, 2026)
Students’ speaking skills in EFL classrooms are often limited by low confidence, limited practice, and less interactive teaching techniques. Therefore, this study aimed to examine the effectiveness of semi-scripted role play in enhancing the speaking skills of EFL students at MAN 1 Palu. This research employed a quantitative, quasi-experimental design with two groups: an experimental and a control group. The participants were 34 eleventh-grade students, with 17 in each group. The experimental group was taught using semi-scripted role play, while the control group received conventional speaking instruction. Data were collected through speaking pre-tests and post-tests assessing students’ fluency, accuracy, and pronunciation. The data were analysed using descriptive statistics, the Shapiro–Wilk normality test, and the Mann–Whitney U test to assess differences between the two groups. The results revealed that students in the experimental group showed greater improvement in speaking skills than those in the control group, and the Mann–Whitney U test indicated a significant difference in post-test scores between the groups at the 0.05 significance level. These findings demonstrate that semi-scripted role-play is an effective teaching technique for improving students’ speaking skills by providing structured support while encouraging active, meaningful communication.